The Influence Of Price Perception And Service Quality On Repurchase Intention Of Grabbike (Survey on UNPER Students Using GrabBike Transportation Services) - Triani, Santi; Askolani; Arif (Utami Publisher, 2024)
This study aims to determine the simultaneous and partial influence of price perception and service quality on Grabbike consumer repurchase intention. The research method used is quantitative with a survey approach to 100 respondents at the University of Perjuangan students who have used Grabbike. The type of data used is primary data and secondary data. The analysis technique used is multiple regression using SPSS version 25. Based on the results of this study, it shows that price perception and service quality simultaneously have a positive and significant effect on repurchase intention. Price perception partially has a significant effect on repurchase intention and service quality partially has a significant effect on repurchase intention of Grabbike users at the University of Perjuangan Tasikmalaya students.